THE INTELLECTUAL TRADITION OF MANDAILING ULAMA IN EAST SUMATRA: Zainal Arifin Abbas, 1912-1979 - Dahlan, Zaini (Journal of Contemporary Islam and Muslim Societies, 2020)
Abstract: The Intellectual Tradition of Mandailing Ulama in East Sumatra: Zainal Arifin Abbas, 1912-1979. This study examines the biography, works and contributions of Zainal Arifin Abbas in East Sumatra. The intellectual activity of Zainal Arifin Abbas’s in East Sumatra is influenced by parents, teachers, colleagues and those around him. This study examines the biography and contribution of Zainal Arifin Abbas in tradition and intellectual dynamics in East Sumatra. Applying a sociological-historical method, this study establishes that Zainal Arifin Abbas have indeed contributed very significantly in the field of education. Through his personal example, he managed to become a wise educator, initiator of the founding of the modern madrasa, and at the same time a prolific writer. He always showed enthusiasm in studying, integrating knowledge, glorifying teachers, and always giving an understanding of the urgency of religious education to the community. He is also an activist and fought for Indonesian independence. Keywords: Mandailing, Ulama, East Sumatra, Zainal Arifin Abbas